KEMAMPUAN BERPIKIR KREATIF DALAM MENYELESAIKAN SOAL OPERASI HITUNG BENTUK ALJABAR DITINJAU DARI PERBEDAAN GENDER - Sasmita Sasmita; Sri Satriani (Universitas Muhammadiyah Makassar, 2022)
This study aims to describe the ability to think creatively in solving arithmetic operations on algebraic forms in terms of gender differences in seventh-grade students of SMP Negeri 3 Sungguminasa. This type of research is a descriptive study with a qualitative approach designed to determine students' creative thinking skills in the subject of arithmetic operations in algebraic forms in terms of gender differences. Data collection techniques in the form of tests and interviews. The instrument used is in the form of a creative thinking ability test, which consists of 2 questions. Interviews were conducted to further explore students' creative thinking skills. The research subjects consisted of 1 female student and one male student. The results showed that the creative thinking ability of female students in solving all algebraic arithmetic operations questions was able to meet two indicators of creative thinking including fluency and flexibility. The ability to think creatively in male students in solving all arithmetic operations questions in algebraic forms is also only able to fulfill two indicators of creative thinking including fluency and flexibility.